Catchment characteristics and seasonality control the composition of microbial assemblages exported from three outlet glaciers of the Greenland Ice Sheet - Vrbická, Kristýna; Kohler, Tyler J.; Falteisek, Lukáš; Hawkings, Jon R.; Vinšová, Petra; Bulínová, Marie; Lamarche-Gagnon, Guillaume; Hofer, Stefan; Kellerman, Anne M.; Holt, Amy D.; Cameron, Karen A.; Schön, Martina; et al. (Frontiers in Microbiology, 2022)
Glacial meltwater drains into proglacial rivers where it interacts with the surrounding landscape, collecting microbial cells as it travels downstream. Characterizing the composition of the resulting microbial assemblages in transport can inform us about intra-annual changes in meltwater flowpaths beneath the glacier as well as hydrological connectivity with proglacial areas. Here, we investigated how the structure of suspended microbial assemblages evolves over the course of a melt season for three proglacial catchments of the Greenland Ice Sheet (GrIS), reasoning that differences in glacier size and the proportion of glacierized versus non-glacierized catchment areas will influence both the identity and relative abundance of microbial taxa in transport. Streamwater samples were taken at the same time each day over a period of 3 weeks (summer 2018) to identify temporal patterns in microbial assemblages for three outlet glaciers of the GrIS, which differed in glacier size (smallest to largest; Russell, Leverett, and Isunnguata Sermia [IS]) and their glacierized: proglacial catchment area ratio (Leverett, 76; Isunnguata Sermia, 25; Russell, 2). DNA was extracted from samples, and 16S rRNA gene amplicons sequenced to characterize the structure of assemblages. We found that microbial diversity was significantly greater in Isunnguata Sermia and Russell Glacier rivers compared to Leverett Glacier, the latter of which having the smallest relative proglacial catchment area. Furthermore, the microbial diversity of the former two catchments continued to increase over monitored period, presumably due to increasing hydrologic connectivity with proglacial habitats. Meanwhile, diversity decreased over the monitored period in Leverett, which may have resulted from the evolution of an efficient subglacial drainage system. Linear discriminant analysis further revealed that bacteria characteristic to soils were disproportionately represented in the Isunnguata Sermia river, while putative methylotrophs were disproportionately abundant in Russell Glacier. Meanwhile, taxa typical for glacierized habitats (i.e., Rhodoferax and Polaromonas) dominated in the Leverett Glacier river. Our findings suggest that the proportion of deglaciated catchment area is more influential to suspended microbial assemblage structure than absolute glacier size, and improve our understanding of hydrological flowpaths, particulate entrainment, and transport.